Comparative Analysis Of The Feasibility Inpari IR Nutri Zinc Paddy Farming With Other Varieties In Nanggulan Sub-district Kulon Progo District - Nafiatunnisa, Galuh; Satyarini, Triwara Buddhi; Rahayu, Lestari (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
Inpari IR Nutri Zinc paddy is New Superior Variety (VUB) paddy which has a high potential content of Zn which can reach 34,51 ppm with an average of 29,54 ppm. This study aims to determine the average cost, revenue, income, and profit of Inpari IR Nutri Zinc, Ciherang, and Inpari 42 Paddy farming and to determine of comparison the average of feasibility of Inpari IR Nutri Zinc Paddy farming with Ciherang and Inpari 42 Paddy farming in Nanggulan Sub-district, Kulon Progo District. The basic method used is descriptive analysis. The sampling method is cluster sampling method with a non-proportional for determining the number of respondents in Jatisarono Village, Nanggulan Sub-district, Kulon Progo District with a total sample of 60 farmers. The average cost per 1.000 m2 of Inpari IR Nutri Zinc, Ciherang, and Inpari 42 Paddy farming in Nanggulan Sub-district respectively is IDR 2.001.362, IDR 1.937.718, and IDR 2.024.216. The average revenue per 1.000 m2 of Inpari IR Nutri Zinc, Ciherang, and Inpari 42 Paddy farming respectively is IDR 2.179.575, IDR 2.545.940, and IDR 2.551.111. The average income per 1.000 m2 of Inpari IR Nutri Zinc, Ciherang, and Inpari 42 Paddy farming respectively is IDR 817.141, IDR 1.171.901, and IDR 1.176.587. The average profit per 1.000 m2 of Inpari IR Nutri Zinc, Ciherang, and Inpari 42 Paddy farming respectively is IDR 178.213, IDR 608.222, and IDR 526.895. The average feasibility of Inpari IR Nutri Zinc Paddy farming in terms of R/C, land productivity, labor productivity, and capital productivity are still lower than the feasibility of Ciherang and Inpari 42 Paddy farming.